Construction of high-temperature electronic conduction paths for the scale-up of solid oxide fuel cell technology. Issue 22 (12th May 2022) - Park, Mi Young; Park, Sun-Young; Seo, Haewon; Jung, Jin-Mook; Hwang, Hyo Ki; Hong, Jongsup; Park, Jun-Young; Lee, Insung; Yoon, Kyung Joong
Abstract : Cu–Mn foam provides reliable high-temperature electronic conduction paths via in situ phase transformation for large-scale solid oxide fuel cell stacks. Abstract : Solid oxide fuel cells (SOFCs) currently face great opportunities in various applications. One of the critical issues for their commercialization involves cathode current collection in full-scale stacks because forming a reliable electronic conduction path in high-temperature oxidizing environments is extremely difficult. Herein, we present a Cu–Mn foam as a highly efficient, reliable, and cost-competitive cathode current collector. The Cu–Mn foam exists as a metallic alloy in the as-fabricated state, which offers adequate mechanical properties for stack assembly. Subsequently, it transforms into a conductive spinel oxide during high-temperature operation, providing the desired electrical and structural characteristics. Resistance measurements at 700 °C verify that the Cu–Mn foam was stable for 27 000 h. In unit cell testing, the foam performs comparably to a noble metal (Pt) mesh, and when the cell is enlarged from 4 to 100 cm 2, no performance loss occurs. Furthermore, it is successfully incorporated into a 1 kW-class full-size stack, where it demonstrates excellent durability in accelerated tests involving thermal and current cycling for 3684 h. This developed Cu–Mn foam can overcome a crucial limitation in the scale-up of SOFC technology and can also be utilized to construct high-temperature electronic conduction paths in various applications.